Study Description of The Implementation Volleyball Game Learning - Hilman Nugraha; Bambang Abdul Jabar; Carsiwan Carsiwan; Samsul Bahri (Universitas PGRI Palembang, 2023)
This study was motivated by the researcher's curiosity about how teachers carry out the teaching process of learning volleyball games at the Junior High School level. This study aims to determine the activities of teachers at school how to teach volleyball that the teacher has done so far. The purpose of this study is to determine the teaching of learning carried out by teachers starting from teaching planning, organizing teaching and teaching assessment in teaching volleyball games. The method used in this research is descriptive qualitative method with interview research design. This research is research conducted by making comparisons or connecting with other variables. The results of the study show that the teacher conducts teaching learning according to physical education, the results of the research that has been done can be concluded that good teaching is teaching that pays attention to 3 components of teaching namely planning, organizing and assessing.